(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare muscle balance exercises in a vibratory training method, then to identify the effect of exercises in developing some biomechanical indicators of the skill of the wall of the young players in volleyball for youth. For volleyball from Baghdad clubs (Al-Sina’a Club, Police Club, Al-Mawhiba Specialized School, Salikh Club, Al-Jaish Club) (youth category), which numbered (85) players.The researcher used the accuracy test of the wall, and it included training exercises in volleyball with a total of (24) training units, and the number of training units per week was (3) units, and the unit time was (90) minutes. Between (15-25) minutes from the time of the main part, and after performing the exercises on the device during the prescribed period, the researcher concluded that the exercises of muscular balance in the vibratory training method used were a means of guidance that greatly helped in some of the biomechanical variables under study.